2020
DOI: 10.3906/sag-1906-91
|View full text |Cite
|
Sign up to set email alerts
|

Results of genicular nerve ablation by radiofrequency in osteoarthritis-related chronic refractory knee pain

Abstract: The aim of this study was to investigate the medium-to long-term effects of radiofrequency (RF) ablation of genicular nerves for chronic refractory knee pain due to osteoarthritis (OA). Materials and methods: Forty-eight patients who underwent RF ablation of the genicular nerves were evaluated retrospectively. The visual analogue scale (VAS) score, Western Ontario and McMaster universities osteoarthritis index (WOMAC index), opioid and nonsteroidal antiinflammatory drug (NSAID) use score, quality of life score… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…Two records were not published in English or Chinese. Finally, a total of 20 eligible articles were included in our meta-analysis [ 7 , 9 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two records were not published in English or Chinese. Finally, a total of 20 eligible articles were included in our meta-analysis [ 7 , 9 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…Among 10 articles using conventional RFA, eight recorded adverse effects after treat-ment [ 7 , 13 , 15 , 17 , 18 , 19 , 20 , 21 ]. All of them reported that no serious adverse effects or complications related to conventional RFA were observed.…”
Section: Resultsmentioning
confidence: 99%
“… 1 Knee OA represents one of the most common joint diseases in adults, with a prevalence as high as 40% in adults between the ages of 70 and 75, and remains one of the leading causes of pain and disability in elderly populations. 2 , 3 Overall, the prevalence of knee pain, independent of age and BMI has increased substantially over the past few decades, nearly doubling among women and tripling among men over a 20-year period. 4 Genicular nerve ablation offers an effective, low risk alternative for patients who have failed conservative treatment of their knee pain, such as weight loss, physical therapy, and pharmacotherapy, who may not be good surgical candidates or may prefer to avoid surgery.…”
Section: Introductionmentioning
confidence: 99%
“… 1 The procedure has been shown to offer patients effective pain relief along with improvements in quality of life, daily function, and patient satisfaction, with a low risk of serious side effects. 2 A recent retrospective study conducted by Iannaccone et al found that, on average, genicular nerve ablation offers patients with intractable knee pain 60% pain relief lasting for as long as 6 months. 5 …”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, minimally invasive modalities can be appealing for managing residual post-TKR knee "residual pain" in patients where no identifiable cause is found. Radiofrequency ablation (RFA) of genicular nerves (GNRFA) is gaining popularity as one of the modalities in managing chronic pain in knee osteoarthritis (KOA) and painful TKR [6][7][8][9][10]. Despite a modest number of publications demonstrating the usefulness of GNRFA in managing pain in KOA, the efficacy of GNRFA has not been completely established in the management of residual pain after TKR.…”
Section: Introductionmentioning
confidence: 99%